Warranty Deed, Camden County, 1854 - State of Georgia, Camden County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1854)
Warranty Deed, Camden County, 1854. Deed between Andrew Harrold and Francis Readdick for 194 acres in Camden County, Georgia. May 1, 1854. 2 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Camden County (Ga.); Court Records; Records and correspondence; Trust indentures